Fibrinolysis as Related to the Urea Solubility of Fibrin - Bickford, Arthur F., Jr.; Sokolow, Maurice (Thrombosis and Haemostasis, 1961)
The in vitro experiments described in this report demonstrate that the rate of fibrinolysis as determined by both the spontaneous whole blood fibrinolysis test and the fibrin plate procedure is altered by variations in technique. The addition of calcium ion to the fibrinogen before clotting and the heating of fibrin resulted in similar decreases in fibrinolytic activity. Probably the same mechanism was involved, since both the addition of calcium and heating are known to cause the conversion of hydrogen-bonded fibrin to the sulfhydrylbonded form. The finding of both kinds of fibrin in spontaneously clotted whole plasma and in clots taken from the heart postmortem suggests that the type of fibrin bonding may influence the rate of removal of clots in vivo.